Wybrane metody analizy i prognozowania czasu pobytu na OIOM pacjentów z chorobą wieńcową - Misztal, Małgorzata (Selected Methods for Analysis and Prediction of ICU Length of Stay among Patients With CAD, 2007)
In the paper the dataset of 4642 patients, treated surgically due to coronary artery disease during October 2003 to December 2005 in 12 Polish Cardiac Departments was analysed. The objective of the study was to compare ICU length of stay among patients from different hospitals and an attempt to assess preoperative risk facto associated with prolonged ICU stay on the basis of RIDIT analysis, logistic regression, discriminant analysis and classification and regression trees.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 288-296